Penerapan Model Problem Based Learning untuk meningkatkan Hasil Belajar Matematika Siswa Kelas X.2 SMAN 5 Mataram Tahun Ajaran 2024/2025 - Baiq, Sinta Erviana; Prayitno, Sudi; Savitry , Ite Githa (Griya Journal of Mathematics Education and Application, 2025)
This study aims to improve students' mathematics learning outcomes through the implementation of the Problem Based Learning (PBL) model. The research subjects were 36 students of Class X.2 at SMAN 5 Mataram in the 2024/2025 academic year. The research was conducted as Classroom Action Research (CAR) over two cycles, with each cycle consisting of planning, action, observation, and reflection stages. Data were collected through learning outcome tests at each stage: pre-cycle, cycle I, and cycle 2, and analyzed quantitatively. The results showed an increase in the average student learning outcomes from 5,5% in the pre-cycle, to 38,9% in cycle I, and 80,5% in cycle 2. This improvement indicates that the implementation of the PBL model is effective in enhancing students' mathematics learning outcomes. These findings highlight the importance of applying PBL to create student-centered learning that can meaningful and contextual in the processes.